Pengaruh Strategi Pembelajaran Point Counterpoint Terhadap Hasil Belajar Mata Pelajaran Fiqh Siswa MAN Karanggede Tahun 2014/2015 - Musta’an Musta’an (Jurnal Ilmiah Ekonomi Islam, 2015)
This study is an experimental research conducted at MAN Karanggede. The population in this study were students of class XI which totaled 200, with purposive sampling technique obtained a sample of 90 students. The samples were divided into two groups, the first group as a control group and a second group class as a class experiment. Data was collected by the method of testing and documentation. Test validity consists of 35 items, 31 items known to valid and invalid 4 items. Of the 31 items were valid, the validity of the lowest known 0.399 and 0.722 and the highest validity reliabelitas 0.91. Data prior to analysis prerequisite test, normality test, homogeneity test, tests of balance and analyzed using statistical t-test formula.From the data analysis is concluded that control class (using conventional methods) reached an average value of 48.62 by the level of learning outcomes in the category were as many as 16 students or 35.56% are located at intervals of 13-15. While the experimental group (using learning strategies point counterpoint) reached an average value of 71.97 by the level of learning outcomes in high category as many as 10 students or 22.22% are located at intervals of 22-25. Of the average showed a difference of 23.35. While the results of different test variable levels of learning outcomes fiqh in control class with experimental class obtained t count (5.721)> t table (2.000), it means Ha accepted, so there are significant learning strategy point counterpoint to the results of study subjects fiqh students MAN Karanggede school year 2014 / 2015. Keywords: Learning Strategies Point Counterpoint, Fiqh Learning Outcomes